Diary of a Country Priest: The Transcendent on Film - Avila, Wanda E. (The journal of religion and film, 2006)
Recognized as a masterpiece of French cinema, Robert Bresson's Diary of a Country Priest (1951) dramatizes a young priest's encounters with grace during the months he spends in his first parish in the rural village of Ambricourt. During this time, the priest keeps a journal in which he records both the outer events of his life in Ambricourt and his inner experiences of a transcendent reality. The art of this film lies in its dramatization of these mystical experiences, making viewing the film a spiritual experience for many viewers.